2022
DOI: 10.4240/wjgs.v14.i2.185
|View full text |Cite
|
Sign up to set email alerts
|

Status of bariatric endoscopy–what does the surgeon need to know? A review

Abstract: BACKGROUND Obesity is a chronic and multifactorial disease with a variety of potential treatment options available. Currently, there are several multidisciplinary therapeutic options for its management, including conservative, endoscopic, and surgical treatment. AIM To clarify indications, technical aspects, and outcomes of bariatric endoscopy. METHODS Narrative review of current literature based on electronic databases including MEDLINE (Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Different from several studies, 5,8,14,28 we reported the use of adjunctive endoscopic approaches in a substantial part of our population. This finding is related to our experience in treating these challenging conditions, as described in Methods 27,29–34 . It is important to state that there is no gold standard method to treat TGID.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Different from several studies, 5,8,14,28 we reported the use of adjunctive endoscopic approaches in a substantial part of our population. This finding is related to our experience in treating these challenging conditions, as described in Methods 27,29–34 . It is important to state that there is no gold standard method to treat TGID.…”
Section: Discussionmentioning
confidence: 64%
“…To achieve clinical success, fundamental principles must be applied, such as adequate drainage and treatment of related factors. 1,2,19,23,26,27 For adequate drainage with EVT, the system needs to function. Compared to OPPS, the EVT is not effective when it is not possible to achieve negative pressure and should be considered a contraindication in some conditions such as tracheal-esophageal fistula, rectovaginal fistula, GI-cutaneous fistula, laparostomy, and pleurostomy Intolerance to the NGT followed by sepsis (1) Although rare, patient's intolerance to the tube can occur.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations